(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study investigates the determinants of turnover intention among millennial employees, examining the direct and mediated roles of work-life balance, job stress, and job satisfaction. Data were collected from 180 millennial workers using a saturated sampling technique and analyzed with PLS-SEM. The findings reveal a nuanced model: job stress directly increases turnover intention, whereas work-life balance has no direct effect. Interestingly, both work-life balance and job stress significantly enhance job satisfaction. However, job satisfaction itself does not translate into reduced turnover intention. Consequently, job satisfaction fails to function as a significant mediator. These results challenge conventional models, underscoring the primacy of direct stress management over enhancing job satisfaction as a strategy to mitigate turnover intention in this demographic.